Osamu Tezuka's Buddha, Canonical Authority, and Remix Theory in the Study of Religion. - Walker, Seth M (Journal of the American Academy of Religion, 2022)
Contemporary narrative repositories of religious traditions are often the ambiguous product of dialogic oral transmissions that occurred over many years, undergoing variation based on audience, context, or ideological purpose. Through an application of remix theory, both official and unauthorized narrative developments among the sacred stories of religious traditions can be understood as sampling processes in which select elements are sourced from archival spaces of narrative data in the creation of unique versions for the contexts in which they emerge. This is specifically demonstrated through Osamu Tezuka's Buddha manga series, but the questions it raises and the conceptual challenges it presents for doctrinal notions of authority and authenticity are also relevant outside the immediate context of Buddhism for the canonical traditions within other religious systems. Thus, this article demonstrates how remix theory can be utilized to better challenge the ways such concepts are understood and taken for granted in religious traditions.